2018
DOI: 10.5194/hess-22-4083-2018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen attenuation, dilution and recycling in the intertidal hyporheic zone of a subtropical estuary

Abstract: Abstract. Tidal estuarine channels have complex and dynamic interfaces controlled by upland groundwater discharge, waves, tides and channel velocities that also control biogeochemical processes within adjacent sediments. In an Australian subtropical estuary, discharging groundwater with elevated (> 300 mg N L−1) NH4+ and NO3- concentrations had 80 % of the N attenuated at this interface, one of the highest N removal rates (> 100 mmol m−2 day−1) measured for intertidal sediments. The remaining N was also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…In contrast, in zone A (Figure 1), NO3 ${{\text{NO}}_{3}}^{-}$ concentration in confined water decreases significantly along the flow direction, accompanied by the increase of δ 15 N‐NO3 ${{\text{NO}}_{3}}^{-}$ and δ 18 O‐NO3 ${{\text{NO}}_{3}}^{-}$ and Fe 2+ concentration and the obvious decrease of ORP (Figure 7a). However, NH4+ ${{\text{NH}}_{4}}^{+}$ concentration in groundwater also increases, indicating that the decrease in NO3 ${{\text{NO}}_{3}}^{-}$ concentration might result from DNRA (Lamontagne et al., 2018). As the lakeside floodplain, terrain in zone A is gentle, and a set of sub‐sand and sub‐clay of fluvial and lacustrine facies with a thickness of several meters are generally deposited (Guo et al., 1985).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in zone A (Figure 1), NO3 ${{\text{NO}}_{3}}^{-}$ concentration in confined water decreases significantly along the flow direction, accompanied by the increase of δ 15 N‐NO3 ${{\text{NO}}_{3}}^{-}$ and δ 18 O‐NO3 ${{\text{NO}}_{3}}^{-}$ and Fe 2+ concentration and the obvious decrease of ORP (Figure 7a). However, NH4+ ${{\text{NH}}_{4}}^{+}$ concentration in groundwater also increases, indicating that the decrease in NO3 ${{\text{NO}}_{3}}^{-}$ concentration might result from DNRA (Lamontagne et al., 2018). As the lakeside floodplain, terrain in zone A is gentle, and a set of sub‐sand and sub‐clay of fluvial and lacustrine facies with a thickness of several meters are generally deposited (Guo et al., 1985).…”
Section: Resultsmentioning
confidence: 99%
“…Groundwater NO3 ${{\text{NO}}_{3}}^{-}$ concentration is affected by human activities, biogeochemical processes (e.g., dissimilatory NO3 ${{\text{NO}}_{3}}^{-}$ reduction to NH4+ ${{\text{NH}}_{4}}^{+}$ (DNRA), denitrification, and sorption), and groundwater flow (Archana et al., 2018; Böhlke & Denver, 1995; Hofmeister et al., 2022; Lamontagne et al., 2018; Rivett et al., 2008). Among them, groundwater flow is an important driving force for distribution, migration, and transformation of NO3 ${{\text{NO}}_{3}}^{-}$ in groundwater (Umezawa et al., 2008; Yue et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The length of the porewater flowpath have a large influence on the biogeochemical processes occurring within sediments and on the chemical composition of porewaters discharging across the sediment-water interface (Heiss et al, 2017;Lamontagne et al, 2018;Weinstein et al, 2011). Consequently, the spatial scale of porewater fluxes needs to be considered to evaluate the overall magnitude of solute inputs driven by porewater fluxes.…”
Section: Magnitudes and Temporal Scales Of Driving Forces And Porewatmentioning
confidence: 99%
“…Seawater delivers oxygen and reactive organic carbon to intertidal sediments. Various reactions including aerobic respiration (Anschutz et al, 2009; Charbonnier et al, 2013; Seidel et al, 2015), denitrification (Jiao et al, 2018; Kroeger et al, 2006; Kroeger & Charette, 2008; Lamontagne et al, 2018), and metal transformations (Charette & Sholkovitz, 2002; McAllister et al, 2015; Roy et al, 2010) have been observed in intertidal aquifers, impacting concentrations of solutes discharging to the coastal ocean.…”
Section: Introductionmentioning
confidence: 99%